The Use of Rubber Seed Oil as an Alternative Plant Lipid Source for Stripped Catfish (Pangasianodon hypophthalmus) Diet - Andi Apriany Fatmawaty; Achmad Noerkhaerin Putra; Aris Munandar; Nuniek Hermita; Mustahal Mustahal; Dodi Hermawan; Lukman Anugrah Agung; Arif Rahman; Mas Bayu Syamsunarno (Department of Aquaculture, 2021)
Dietary lipid in the forms of fish oil and corn oil are known as the best lipid sources. An effort to find an alternative to lipid sources other than both forms of oil can be done through the use of ts rubber seed oil. The study was conducted to evaluate rubber seed oil as a lipid source in the diet for increasing the growth of striped catfish (Pangasianodon hypophthalmus) fingerlings. A tested diet having isoprotein (30.14±0.01%) and isoenergy (271.26±0.08 DE kcal/100g) was used in this study. Fish oil, corn oil, and rubber seed oil at a total of 3% were used as the diet's lipid sources. Rubber seed oil was added to the diet at 0, 1, and 3%, respectively. After acclimatized to the experimental condition, striped catfish fingerlings (9.72±0.01 g) were randomly stocked in 12 aquariums (69x29x35 cm3; Volume 50 L) with a density of 15 fingerlings/container and fed on the tested diet at satiation for 40 days. The use of rubber seed oil as a source of lipid in the diet does not affect the survival rate and body fat (P> 0.05). The composition of 2% rubber seed oil in the feed gives the best growth in striped catfish fingerlings, with feed intake of 233.00±1.00 g, a specific growth rate of 2.01±0.05% day-1, feed efficiency of 75.45 ± 1.18%, protein efficiency ratio of 2.45 ± 0.11% and body protein of 44.03 ± 2.42%. There is a tendency that higher rubber seed oil content in the diet, produce better the fatty acid profile in the body of the striped catfish.